Assessment of Postural Discomfort among Female Sewing Machine Operators - Gahlot, Neha; Mehta, Manju; Singh, Kiran (International Journal of Bio-resource and Stress Management, 2023)
Today women are called upon to undertake the dual role of looking after the family and its needs and also earn for the families maintenance, by taking up either full or part time work for wages. In the process of economic development, women’s role has been a major component. The sewing operation is characterized by a static sitting posture, a forward inclined posture of the head and trunk, and relatively uncomfortable ankle and knee angles. The sewing task includes simultaneous hand and arm movements, and the continuous operation of foot pedals. Poor posture of the trunk, neck and upper extremities, and the monotonous repetitive movements result in a high prevalence of musculoskeletal complaints affecting the backs, necks, upper and lower extremities among sewing machine operators. The study was carried out with the objective to assess the postural discomfort of the hand operated female sewing machine operators who work at their home. The physically fit respondents were selected for the study. A record sheet was developed for record the angle of deviation of cervical and lumbar region taken with flexi curve. Rapid upper limb assessment method (RULA) was used to identify the upper limb disorders of female sewing machine operators. The results of the study showed that the respondents were facing postural discomfort while working, so the study suggested to correct the posture and reduce the angle of deviation during sewing activity.